Reducción de demoras por abastecimiento de combustible, para incrementar la utilización de equipos de acarreo en mina – Summa Gold Corporation - Oliva Sandoval, , Veronica Ysabel (2023)
This research demonstrated the feasibility of reducing delays during fueling to increase the utilization of mine haulage equipment – Summa Gold Corporation. For this purpose, this is applied research, with a quantitative study methodology, not experimental, since we worked with representative samples of historical data, in which, through statistical analysis, the unproductive times and the consequences of these in the use of the equipment were determined. With the analysis it was observed that the supply of fuel was the cause of low use of tippers, because going to fuel a tipper took a time of 67.6 minutes per day of work, since there was only one supply point in mine. This is how satellite supply points were implemented, distributed in strategic places of the mine, so that the tippers no longer leave their work route. Finally, it was possible to reduce the supply time by 84.56%, from 33.8 to 5.22 minutes per tipper; managing to increase the use of tippers by 19% from 73% to 92% utilization.